ACTIVITY-DEPENDENT DEPRESSION OF MEDIAL PREFRONTAL CORTEX INPUTS TO ACCUMBENS NEURONS BY THE BASOLATERAL AMYGDALA - McGinty, V. B. (2009)
The encoding of reward-predictive stimuli by neurons in the nucleus accumbens (NAcc) depends on integrated synaptic activity from the basolateral amygdala (BLA) and medial prefrontal cortex (mPFC) afferent inputs. In a previous study, we found that single electrical stimulation pulses applied to the BLA facilitate mPFC-evoked spiking in NAcc neurons in a timing-dependent manner, presumably by a fast glutamatergic mechanism. In the present study, the ability of repetitive BLA activation to modulate synaptic inputs to NAcc neurons through dopamine- or N-methyl-d-aspartate (NMDA)-dependent mechanisms is characterized. NAcc neurons receiving excitatory input from both mPFC and BLA were recorded in urethane-anesthetized rats. Train stimulation of the BLA depressed mPFC-evoked spiking in these neurons. This was not attributable to mechanisms involving NMDA or dopamine D1, D2, D3 or D5 receptors, since blockade of these receptors did not affect the BLA-mediated depression. BLA-mediated depression was only evident when the BLA stimulation evoked spikes in the recorded neuron; thus, depolarization of the recorded neuron may be critical for this effect. The ability of the BLA to suppress mPFC-to-NAcc signaling may be a mechanism by which normal or pathologically heightened emotional states disrupt goal-directed behavior in favor of emotionally-driven responses.